The crisis of the Arab regional system between internal reforms and external interventions - صبیحة كاظم داود (College of Education for Women, 2019)
Passes the Arab order moment political precision of disruption and discord and differences of countless between its components and its parts because of the suffering he endured and the suffering now from internal disturbances as a result of lack of cohesion relations intra-and cultural, historical and lack of interaction between these components so that became the focus of the policies and interests is an unprecedented degree , reduced with the joint Arab action to the minimum, and began to focus on the interests of special regulations. This is with regard suffering internally, but externally the regime Arab Regional is absent the biggest influence on international decisions because of the courtesies which were carried out at the expense of causes, which came courtesy and concessions as a result of being under full control of regional powers and international organizations of the United States of America and before the United Kingdom and its allies. , the Arab system, both regional and internal mobility is witnessing a large and impressive, and as a result of internal pressure and external, and many of the challenges and rapid changes, which revealed the failure of Arab regimes in the management of political crises of internal and external. On the other hand all the Arab people's ambition and hope that the rise Arab regional system to a level that achieves the self-Arab, away from all selfinterest, personal, and this requires hard work and fixed a bug within the system and within the governing same absent democracy and human rights, and what happened in Tunisia sister of the projection of the regime, and was followed in Egypt, and the reaction of the Arab masses in most of the precincts is nothing but a clear and strong will to abandon the Libyan political system, if it amounts to a roiling torrent.